The Influence of Green Marketing Communication and Brand Credibility through the Mediation of Environmental Attitudes and Moderation of Income Levels on Purchasing Decisions of Green Marketing Products in Aceh - Maimunah, Siti; ., Maisyura; Nainggolan, Khusnul Kotimah; Nisa, Nadiatun (Journal of Ecohumanism, 2024)
The issue of environmental sustainability has become increasingly important, particularly in the context of green product marketing, making it crucial to understand the factors that influence green product purchasing decisions. This study aims to clarify how brand credibility and green marketing communication affect consumer behavior through environmental attitudes and the moderating impact of income levels. Primary data from 300 green product consumers, gathered via a structured questionnaire and analyzed using Structural Equation Modeling (SEM-PLS), reveal several key findings. Brand credibility significantly enhances both environmental attitudes and purchasing decisions, with environmental attitudes playing a critical mediating role in these relationships. Green marketing communication also positively impacts environmental attitudes and purchasing decisions. Additionally, income levels positively affect purchasing decisions but negatively moderate the interaction between environmental attitudes and purchasing decisions. These results underscore the essential role of environmental attitudes in mediating the effects of brand credibility and green marketing communication on purchasing decisions, as well as the nuanced influence of income levels on consumer behavior regarding sustainable products.